Integrating aesthetic considerations in set-based bridge design - A methodfor including qualitative values alongside quan titative objectives in early-stage concrete bridge design - Dahlgren, Matilda; Ellen, Nyholm (My University, 2026)
Early-stage bridge design involves balancing several objectives, including cost, envi ronmental impact, and aesthetic quality. Set-based design combined with parametric modeling can support this phase by generating and comparing many design alternatives. Previous applications have mainly focused on quantitative criteria, such as production cost and environmental impact, while aesthetic aspects are often assessed separately or given less systematic attention. This thesis investigated how aesthetic considerations can be incorporated as qualitative criteria within a set-based design process for concrete bridges. The study was based on a literature study, consultations with professionals, and the de velopment and assessment of a digital prototype. Aesthetic principles relevant to early stage bridge design were identified and translated into criteria that could be handled within a computational model. The prototype was developed for a two-span concrete slab frame bridge and used to generate, filter, evaluate, and visualize design alternatives. The alternatives were assessed with respect to production cost, CO2-equivalent emis sions, and quantified aesthetic criteria. The aesthetic criteria were based on selected ge ometric relationships, such as proportions, symmetry, and variation of structural depth along the span. The thesis proposes a set-based design method that considers qualitative values along side quantitative objectives in early-stage concrete bridge design. The prototype as sessment showed that the inclusion of aesthetic criteria added an additional evaluation dimension to the design space, making trade-offs between production cost, environ mental impact, and selected aesthetic principles more visible. The proposed method should be understood as decision support rather than as an automatic design generator, supporting comparison, visual assessment, and professional judgment in early-stage de sign decisions.
Keywords: set-based design, bridge design, bridge aesthetics, qualitative criteria, parametric de sign, early-stage design